Psychological, Social and Financial Impacts of COVID-19 on Clinical Practices and Academic Activities of Pakistani Ophthalmologists: Doi: 10.36351/pjo.v37i1.1121 - Iqbal, Muhammad Saeed; Latif, Kanwal (Pakistan Journal of Ophthalmology, 2020)
Purpose: To assess the psychological, social and financial impacts of Coronavirus disease of 2019 (COVID-19) on clinical practices and academic activities of ophthalmologists throughout Pakistan. Study Design: Cross sectional survey. Place and Duration of Study: Ophthalmology Department, Sir Syed College of Medical Sciences & Hospital, Karachi. Methods: A self-designed survey was conducted among eye care practitioners working in various regions of Pakistan by using the online survey application named www.surveymonkey.com. The survey consisted of a 10-item questionnaire conceptualized to assess the mental health of ophthalmologists and their social and financial concerns during current COVID-19 pandemic. Data collection included the demographics details, questions assessing the psychological, financial and social influences of COVID-19 and strategies to combat the current situation. Results: Total of 360 valid responses were received. The individual response data was descriptively presented in frequencies and percentages without statistical analysis. Despite online facilities, 57.50% accepted that COVID has brought strain on academic activities. Eighty-eight percent ophthalmologists described decrease patient’s volume and surgeries as the main reasons of reduced income. Majority (72.50%) had closed the services due to fear of getting infected. To the solutions for reducing the viral spread, 60% favored to deal only with emergencies and vision-threatening diseases, 27.50% supported the continuity of all ophthalmic services and only 5% opted to ban the clinical work. Conclusion: Majority of the ophthalmologists were psychologically and financially stressed during COVID-19 and had fearful concerns regarding their clinical practices and academic activities. Key Words: COVID-19, Pakistan, Ophthalmologists, Clinical Practice.